2021
DOI: 10.1080/1331677x.2021.1875254
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reference point method with probabilistic linguistic information based on the regret theory for public health emergency decision-making

Abstract: Group emergency decision-making is an uncertain and dynamic process, in which the decision makers may be bounded rational and have a risk appetite. To depict the vague qualitative assessments, the probabilistic linguistic term sets are employed to express the perceptions of decision makers. First, considering the regret-aversion of the decision makers' psychological characteristic, the value function and the regret-rejoice function in the regret theory are modified to adapt the probabilistic linguistic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In terms of the co-citation network analysis, the most influential paper is Ref. [ 66 ] as it has been cited most by other documents in the EDM field. In addition, Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the co-citation network analysis, the most influential paper is Ref. [ 66 ] as it has been cited most by other documents in the EDM field. In addition, Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emergency decisions may have potentially serious risks since a wrong decision may result in unexpected catastrophic consequences [5,39,65]. Therefore, a lot of studies have been performed on emergency management and the EDM problems have attracted more attention from both researchers and practitioners in the past few years [2,11,14,16,33,34,66,69].…”
Section: Introductionmentioning
confidence: 99%
“…One of the significant characters of the emergency response is timeliness, which means that the rescue teams are asked for taking effective actions during a short time [ 5 , 6 ]. In the process of dealing with an emergency event, inadequate decision information and tight time pressure make it difficult for decision makers to make a reasonable and efficient choice under an unpredictable decision environment [ 7 , 8 ]. Consequently, it is of great significance to develop systematic and reliable EDM methods for determining the optimal response to an emergency event to minimize economic losses and casualties [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2021) developed a multi-dimensional methodology with nested PLTSs and applied it to corporate investment. Xue et al (2021) demonstrated a dynamic reference point method with probabilistic linguistic information based on the regret theory for public health emergency decision-making. Wei et al (2021) suggested probabilistic linguistic multiple attribute group decision making for location planning of electric vehicle charging stations based on the generalized Dice similarity measures.…”
Section: Introductionmentioning
confidence: 99%